On solving the kinematics and controlling of origami box-shaped robot - Thai, Phuong Thao; Nguyen, Ngoc Hai (Institute of Advanced Engineering and Science, 2023)
Nowadays, there are various research on transformable robot. The use of origami pattern for transformable robot can be found in many research. The disadvantages of traditional origami model are the suitable material for folding is zero thickness, complicated patterns and overconstrained mechanism. In this paper, the idea of designing 1 degree-of-freedom box-shaped robot is proposed and two types of robot design have been analyzed. The first design is the waterbomb robot, that uses the traditional origami pattern. The second model takes the Sarrus linkage as the main mechanism for the mobile robot. In both designs, only one motor is required for the transformation of the robot, making the robot light-weight and portable. This paper analyzes the kinematic and dynamic properties of two transformable robots by using MATLAB. The comparison of the torque required for forming 3D shape has been done for optimizing robot design. Finally, the real model optimized design is introduced to illustrate the proposed method.